Influence of Technological Process Parameters on Microcapsulation of Substances with Unsatisfactory Technological Properties - I. D. Kasymov; A. L. Marchenko; A. V. Basevich; M. E. Valeeva (Разработка и регистрация лекарственных средств, 2023)
Introduction. The article presents the results of a study of the influence of parameters of microcapsulation on the properties of microcapsules obtained by diffusion of an emulsion solvent. The results obtained made it possible to establish optimal parameters of the process, such as the mixing speed, the type of mixing device, the volume of the aqueous phase, the concentration of the polymer in the oil phase, the ratio of medicinal substance : polymer, temperature conditions.Aim. The aim of the work was to study the influence of the parameters of the microcapsulation process on the properties of microcapsules obtained by diffusion of an emulsion solvent.Materials and methods. Ibuprofen was used as a model substance for microcapsulation. Eudragit® RS 100 was chosen as the carrier polymer. To assess the shape and nature of the microcapsule surface, a microscope Levenhuk D80L LCD was used, and the size of microcapsules was determined using a laser particle analyzer Microsizer 201C (VA Instalt, Russia).Results and discussion. The influence of the parameters of the microcapsulation process on the properties of ibuprofen microcapsules as a model substance obtained by diffusion of an emulsion solvent has been studied. The optimal parameters of the technology are established, the dependences between the critical parameters of microcapsulation and the properties of the resulting microcapsules are determined.Conclusion. In the course of the study, the choice of technological parameters of microcapsulation by diffusion of an emulsion solvent was proposed and justified. The experimental data obtained on the example of ibuprofen as a model substance will be used as the basis of the experiment when preparing microcapsules based on other substances soluble in organic solvents.